Pentingnya Sosialisasi Guna Meningkatkan Pemahaman Keamanan Informasi di Kelurahan Serua, Depok - Syahrul Salam; Ali Zhafir Talmullah; Rahmadini Agung Ayu Utami (CV. Multi Kreasi Media, 2023)
The rapid development of digitalization has had an impact on the rise of crime in cyberspace. Technological sophistication that allows the free exchange of information via internet networks allows criminal acts on the internet or cyberspace to become increasingly diverse. The large number of crimes committed by criminals using computer technology and internet networks means that socialization is considered important to build public awareness. People who understand information security can protect their personal information and prevent misuse of information in cyberspace. The method used in this service through outreach is Community Based Research (CBR) which involves the active role of students and lecturers by including the help of community organization groups. The outreach carried out by the service team aims to increase participants' understanding of the importance of maintaining information security. This outreach is useful for minimizing the potential for spreading detrimental information. The results of the evaluation of socialization activities show an increase in participants' understanding and awareness of the importance of being careful in disseminating various information on the internet, both personal information and news information. In this way, the service team hopes that the material presented to participants in the socialization activities will be applied in everyday life and make them more careful and critical in using various information in cyberspace.